Compensation method for the influence of angle of view on animal temperature measurement using thermal imaging camera combined with depth image. (December 2016) - Jiao, Leizi; Dong, Daming; Zhao, Xiande; Han, Pengcheng
Abstract: In the study, we proposed an animal surface temperature measurement method based on Kinect sensor and infrared thermal imager to facilitate the screening of animals with febrile diseases. Due to random motion and small surface temperature variation of animals, the influence of the angle of view on temperature measurement is significant. The method proposed in the present study could compensate the temperature measurement error caused by the angle of view. Firstly, we analyzed the relationship between measured temperature and angle of view and established the mathematical model for compensating the influence of the angle of view with the correlation coefficient above 0.99. Secondly, the fusion method of depth and infrared thermal images was established for synchronous image capture with Kinect sensor and infrared thermal imager and the angle of view of each pixel was calculated. According to experimental results, without compensation treatment, the temperature image measured in the angle of view of 74° to 76° showed the difference of more than 2 °C compared with that measured in the angle of view of 0°. However, after compensation treatment, the temperature difference range was only 0.03–1.2 °C. This method is applicable for real-time compensation of errors caused by the angle of view during the temperature measurement process with the infrared thermal imager. Highlights: First study to combine thermal image with depth image. Compensate the influence of the angle of view when using IR for temperature measurement. The accuracy of temperature measurement of animal using IR was enhanced.